COMBINING MULTIPLE DISINFORMATION COUNTERMEASURES TO REGULATE ELECTION DISRUPTIONS: THE SOUTH KOREAN CASE - Ahn, Soyun (AoIR Selected Papers of Internet Research, 2020)
Disinformation spread through social media has been widely detected around the world in recent years. Researchers, the press, and the public alike have expressed strong concerns about disinformation influencing public discourse and elections, perceiving it as a direct threat to democracy. Democratic countries once reluctant to restrict freedom of speech are now actively examining countermeasures to disinformation. Such measures could be divided into four categories: Regulating platforms, criminalization of offenders, governmental monitoring, and relying on civil society. The existing literature so far has focused more on examining the pros and cons of individual policy directions rather than providing an overview of the entire dynamics when multiples measures are combined in practice. It is due to most countries still being at their infancy discussing and inventing a disinformation regulation suitable for their legal freedom of speech protection structure. South Korea is unique in that it has operated a system dealing with disinformation for over a decade now, and in that it has a system specifically dedicated to election protection combining three of the four measures introduced above. Through scrutinizing both the legal framework and execution practices of the multiple disinformation countermeasures in South Korea, this research expands the existing literature by offering insights on how combining measures could result in unforeseen discounts of freedom of speech.